2018
DOI: 10.1186/s40359-018-0241-4
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Greek translation of the Job Satisfaction Survey (JSS)

Abstract: BackgroundJob satisfaction is fundamental to employee well-being and successful operation of an organization. The use of effective tools for assessing it is imperative for management research. Our main purpose was to translate and adapt the Job Satisfaction Survey (JSS) questionnaire to the Greek language and to test its psychometric properties.MethodsThe tool was translated into Greek and then back into English by different bilingual translators. The Greek JSS was tested with a sample of 239 employees of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 19 publications
4
40
0
2
Order By: Relevance
“…On the bases of the local actual condition, we collected the job satisfaction information using an Adjusted Satisfaction Scale. The adjusted scale referred for the Minnesota Satisfaction Questionnaire, 21 Job Satisfaction Survey 22 and Job Descriptive Index, 23 Open access points (the most satisfaction). A higher score indicates a higher satisfaction.…”
Section: Methods Of Measurement Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the bases of the local actual condition, we collected the job satisfaction information using an Adjusted Satisfaction Scale. The adjusted scale referred for the Minnesota Satisfaction Questionnaire, 21 Job Satisfaction Survey 22 and Job Descriptive Index, 23 Open access points (the most satisfaction). A higher score indicates a higher satisfaction.…”
Section: Methods Of Measurement Job Satisfactionmentioning
confidence: 99%
“…On the bases of the local actual condition, we collected the job satisfaction information using an Adjusted Satisfaction Scale. The adjusted scale referred for the Minnesota Satisfaction Questionnaire, 21 Job Satisfaction Survey 22 and Job Descriptive Index, 23 including 14 items (items 1–14) about the satisfaction with the internal environment, external environment, remunerations, management and work itself. Participants responded to a 5-point Likert Scale ranging from 1 point (the most unsatisfaction) to 5 points (the most satisfaction).…”
Section: Methodsmentioning
confidence: 99%
“…Job satisfaction is an important variable and predictor of wellness in the work environment. It has a profound impact on the productivity and the effectiveness of the services (Tsounis & Sarafis, 2018). A study showed that empowerment, physician–nurse relationship and organizational support/trust were the most important predictors of job satisfaction (Kretzschmer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of these factors results in satisfied employees (Baylor, 2010). Intrinsic job satisfaction refers to employees' feelings toward the nature of the job tasks, for example, achievement and control, success, ability to develop skills, and sense of autonomy (Tsounis & Sarafis, 2018;Abdallah et al, 2016). Intrinsic motivation appears from within the employees, and is described as the willingness to do more in order to fulfill tasks (Almomani, 2018).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…According to Herzberg (1966), the existence of extrinsic job satisfaction factors (or hygiene factors), may not necessarily mean that employees are satisfied; however, their absence might be dissatisfying for employees (Baylor, 2010). Extrinsic job satisfaction refers to employees' feelings toward various aspects of the work situation that are not related to the work itself; for example, quality of the job environment, promotion opportunities, relationships with colleagues, and salary (Tsounis & Sarafis, 2018). According to Abdallah et al 2016, these factors are related to employees' feelings regarding the job conditions and situations.…”
Section: Job Satisfactionmentioning
confidence: 99%